Long-term response of China hybrid tea (Camellia sinensis) to nitrogen, phosphorus and potassium in Himachal Pradesh - Sharma, K L; Sharma, D K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducred during 1975-90 to study long-term response of China hybrid tea[Camellia sinensis (L.) O. Kuntze] to N, P and K. A 120-year-old China hybrid tea sectionwas fertilized with N @ 0, 90 and 180 kg/ha (N0, N90 andN180); P@ 0, 39 and 78 kg/ha (P0, P39 and P78);and K @ 0, 33 and 66 kg/ha (K0, K33 and K66). On the basisof 16-year average an increase in yield of 74.4, 32.8 and 40.5% was recorded withN90, P39 and K33 respectively. Significant responses wereobserved when N and P were applied with K. The fertilizer combinations ofN90K66 and P78K66 increased the yield by 108.1and 39.9% respectively compared with the control. The maximum increase in yield (155.1 %compared with the control) was recorded with combination ofN180P78K33.